Zeolitic Imidazolate Frameworks Derived Co9S8/Nitrogen‐Doped Hollow Porous Carbon Spheres as Efficient Bifunctional Electrocatalysts for Rechargeable Zinc–Air Batteries. Issue 2 (26th October 2022) - Liu, Ting; Peng, Jiayao; Xu, Yuting; Huang, Jianlin
Abstract: The development of nonprecious metal‐based electrocatalysts with remarkable catalytic activity and long‐cycling lifespan toward oxygen reduction reaction (ORR) and evolution reaction (OER) is especially important for rechargeable zinc–air batteries (ZABs). Herein, monodispersed Co9 S8 nanoparticles embedded in nitrogen‐doped hierarchically porous hollow carbon spheres (Co9 S8 NPs/NHCS) are synthesized through a template‐assisted strategy followed by a co‐assembly, thermal annealing, and sulfurization process. Benefiting from larger specific surface area, hierarchically porous hollow structure, and carbon nanotubes self‐growth, the obtained Co9 S8 NPs/NHCS‐0.5 electrocatalyst exhibits decent performance for ORR ( E 1/2 =0.85 V) and OER ( E10 =1.55 V). A rechargeable ZAB assembled using the Co9 S8 NPs/NHCS‐0.5 as air cathode delivers a maximum power density of 116 mW cm −2, high open circuit voltage of 1.47 V, and good durability (no obvious voltage decay after 1200 cycles (200 hours)). Such a hierarchically porous hollow structure of Co9 S8 NPs/NHCS‐0.5 provides a confined space shell and an interconnected hollow core to achieve outstanding bifunctional catalytic activity and cycling stability, which surpass the benchmark Pt/C‐RuO2 . Abstract : Nitrogen‐doped hierarchically porous hollow carbon spheres decorated with monodispersed Co9 S8 nanoparticles (Co9 S8 NPs/NHCS) are synthesized based on the template‐assisted strategy, which exhibits excellent performance toward rechargeable zinc‐air batteries.